Long-term effects of the gait treatment using a wearable cyborg hybrid assistive limb in a patient with spinal and bulbar muscular atrophy: a case report with 5 years of follow-up - Iijima, Kensuke; Watanabe, Hiroki; Nakashiro, Yuichi; Iida, Yuki; Nonaka, Michio; Moriwaka, Fumio; Hamada, Shinsuke (Frontiers in Neurology, 2023)
Background Spinal and bulbar muscular atrophy (SBMA) is a progressive neuromuscular degenerative disease characterized by the degeneration of lower motor neurons in the spinal cord and brainstem and neurogenic atrophy of the skeletal muscle. Although the short-term effectiveness of gait treatment using a wearable cyborg hybrid assistive limb (HAL) has been demonstrated for the rehabilitation of patients with SBMA, the long-term effects of this treatment are unclear. Thus, this study aimed to investigate the long-term effects of the continued gait treatment with HAL in a patient with SBMA. Results A 68-year-old man with SBMA had lower limb muscle weakness and atrophy, gait asymmetry, and decreased walking endurance. The patient performed nine courses of HAL gait treatment (as one course three times per week for 3 weeks, totaling nine times) for 5 years. The patient performed HAL gait treatment to improve gait symmetry and endurance. A physical therapist adjusted HAL based on the gait analysis and physical function of the patient. Outcome measurements, such as 2-min walking distance (2MWD), 10-meter walking test (maximal walking speed, step length, cadence, and gait symmetry), muscle strength, Revised Amyotrophic Lateral Sclerosis Functional Assessment Scale (ALSFRS-R), and patient-reported outcomes, were evaluated immediately before and after gait treatment with HAL for each course. 2MWD improved from 94 m to 101.8 m, and the ALSFRS-R gait items remained unchanged (score 3) for approximately 5 years. The patient could maintain walking ability in terms of gait symmetry, walking endurance, and independence walking despite disease progression during HAL treatment. Conclusion The long-term gait treatment with HAL in a patient with SBMA may contribute to the maintenance and improvement of the gait endurance and ability to perform activities of daily living. The cybernics treatment using HAL may enable patients to relearn correct gait movements. The gait analysis and physical function assessment by a physical therapist might be important to maximize the benefits of HAL treatment.